Analyzing Headline Framing in the 2019 Presidential Election Media Coverage: Menganalisis Pembingkaian Judul Berita pada Liputan Media Pemilihan Presiden 2019 - Rangga Fadilla; Sufiyanto Sufiyanto (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to analyze the headline coverage of Jawa Pos and Kompas newspapers on the April 16 and April 18, 2019 editions, during the Indonesian Presidential and Vice Presidential Election. Employing a qualitative descriptive method, the research focuses on structured observation and writing processes, incorporating Robert N. Entman's framing analysis theory. The findings indicate that both Jawa Pos and Kompas exhibit impartiality towards the presidential candidates, presenting neither bias towards candidate pairs nor indications of favoritism. This neutrality is discerned through a lack of elements reflecting preference in the news coverage provided by both newspapers. The study contributes to the understanding of media dynamics in shaping perceptions during crucial political events. Highlights : The study explores the framing of headlines in Jawa Pos and Kompas during the 2019 Presidential Election, shedding light on media portrayal of political events. Notable findings reveal a lack of bias or preference towards any candidate pair, showcasing media neutrality in reporting the election. Utilizing Robert N. Entman's framing analysis theory, the research offers insights into the nuanced dynamics of media influence on public perception during significant political moments. Keywords: Election Framing, Media Neutrality, Presidential Election, Headline Analysis, Robert N. Entman